2000
DOI: 10.1097/00001756-200008030-00010
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of c-Fos following administration of two tremorgenic agents

Abstract: The regional distribution of c-Fos expression in the brain after the administration of two tremorgenic agents was studied. In both the harmaline- and oxotremorin-treated rats, c-Fos-positive neurons were extensively distributed in the basal ganglia nuclei and the cerebellum. Additionally, in the harmaline-treated rats, numerous c-Fos-positive neurons were also distributed throughout the inferior olivary nucleus. In the oxotremorine-treated rats, while the inferior olive was not involved, c-Fos was strongly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Studies of animal models of tremor have reported wide-spread, or even global, rhythmic oscillations (at 8-12 Hz) among inferior olive neurons induced by harmaline (De and Lamarre, 1973; Batini et al , 1979; Bernard et al , 1984; Miwa et al , 2000). Yet, harmaline does not induce OPT (Kane and Thach, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of animal models of tremor have reported wide-spread, or even global, rhythmic oscillations (at 8-12 Hz) among inferior olive neurons induced by harmaline (De and Lamarre, 1973; Batini et al , 1979; Bernard et al , 1984; Miwa et al , 2000). Yet, harmaline does not induce OPT (Kane and Thach, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-HT can cross-regulate acetylcholine release in the brain (Jackson et al, 1988; Jäkälä et al, 1992; Sparks et al, 2018) and harmaline also binds to other neurotransmitter receptors (norepinephrine, dopamine, glutamate receptors; Glennon et al, 2000; Miwa et al, 2000; Grella et al, 2003; Beitz and Saxon, 2004; Kralic et al, 2005; Paterson et al, 2009) This whole excessive alteration of the neurotransmitter systems may be related in the present data to decreased attention and learning observed after chronic Ayahuasca exposure. In fact, both chronic groups C0.1 and C0.5 presented reduced exploration time, and discrimination index significantly inferior to the control and acute groups.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillation frequency in this tremor decreases with increasing weight of an animal and is equal to 11–14 Hz in mice, 10–12 Hz in rats, and 8–10 Hz in monkeys [18]. Although a synchronous activation of the olivo-cerebellar pathway and release of glutamate in the cerebellum which acts at NMDA and AMPA receptors has been suggested to be a primary cause of the harmaline-induced tremor [18, 22, 23], the mechanisms underlying this symptom seem to be complex and may involve also noradrenergic, serotonergic, dopaminergic, and GABA-ergic systems [2326], as well as some distant brain structures, e.g., reticular formation, caudate–putamen, frontal cortex, and others [27–29]. The latter assumption is based on the fact that a systemic harmaline administration in tremorgenic doses induces metabolic and neuronal activation in the above structures [27–29].…”
Section: Introductionmentioning
confidence: 99%
“…Although a synchronous activation of the olivo-cerebellar pathway and release of glutamate in the cerebellum which acts at NMDA and AMPA receptors has been suggested to be a primary cause of the harmaline-induced tremor [18, 22, 23], the mechanisms underlying this symptom seem to be complex and may involve also noradrenergic, serotonergic, dopaminergic, and GABA-ergic systems [2326], as well as some distant brain structures, e.g., reticular formation, caudate–putamen, frontal cortex, and others [27–29]. The latter assumption is based on the fact that a systemic harmaline administration in tremorgenic doses induces metabolic and neuronal activation in the above structures [27–29]. Moreover, since harmaline has been found to modulate postural tremor induced by a lesion of the substantia nigra in monkeys [30], some interrelationship between neuronal alterations triggered by harmaline and those underlying tremor induced by degeneration of dopaminergic neurons may be suggested.…”
Section: Introductionmentioning
confidence: 99%